Development of a Scientific-Based E-Module Using Sigil Software for the Static Fluids Topic at SMA Negeri 1 Selesai - Dra. ratna Tanjung, M.Pd; Rizky Dwiyanti Panggabean (JURNAL IKATAN ALUMNI FISIKA, 2026)
This research aims to (1) determine the level of validity of developing a Scientific-based physics e-module on Static Fluid material, (2) determine the feasibility level of developing a Scientific-based physics e-module on Static Fluid material, (3) determine student responses to the e-module Scientific based physics on Static Fluid material. The subjects in this research were students of class XI MIA 1 SMA Negeri 1 Selesai, totaling 30 students. This type of research is development research or Research and Development (R&D) using ADDIE. The instruments used in this research consisted of validation questionnaires for material experts and media experts, teacher response questionnaires and student response questionnaires to scientific-based e-modules, and test instruments. The data analysis technique used in this research is descriptive. The results of this research are as follows (1) a scientifically based e-module has been produced which is valid for use as a learning medium, in terms of validation from material experts with a percentage of 88.7% and media experts with a percentage of 91.4%. (2) the level of practicality of the scientific-based experimental video media that has been developed is very practical. The response from one of the subject teachers obtained a percentage of 93.7%. The students' responses in the limited trial involving 10 respondents with a presentation of 81.8% were included in the very practical criteria. Meanwhile, in a wide trial involving 30 respondents, a presentation of 83.1% was obtained with very practical criteria (3) the level of effectiveness of the scientifically based e-module on static fluid material in high school that had been developed was in the high category. This is based on the average N-gain result of 0.73. So it is concluded that the e-module can be declared valid, practical and suitable for use.